The Effect of Trade Openness on Economic Growth Evidence from Arab Countries: - Boudiaf, Hafid (Acta Universitatis Danubius. Œconomica, 2024)
This study dealt with the impact of trade openness on economic growth in the Arab countries, using the panel data analysis approach, trade openness was expressed by the sum of exports and imports as a percentage of GDP, while economic growth was expressed as per capita GDP. The results of the estimation proved the existence of a positive impact of trade openness on economic growth for the Arab countries in all the estimated models, which means that trade openness is one of the most important determinants of economic growth in Arab countries, this is due to the dependence of many of its economies on commercial revenues from oil.